SA-RPL: a scheduling-aware forwarding mechanism in RPL/TSCH-operated networks. (28th May 2020) - Afshari, Saeid; Nassiri, Mohammad; Mohammadi, Reza
Wireless sensor networks have shown to be a promising technology for industrial automation in which continuous monitoring is a critical requirement. Deploying an energy-aware sensor network permits increasing the network lifetime and prolonging the monitoring operation. IEEE 802.15.4e and RPL have been used as de-facto protocols at the access and network layer in low power and low-rate wireless networks. Specifically, the time slotted channel hopping (TSCH) of 802.15.4e has been designed to provide a reliable access method in low power and lossy networks. More importantly, the combination of TSCH and RPL facilitates providing load-balancing together with energy-saving in such networks. This paper proposes schedule aware RPL (SA-RPL) which aims at prolonging the network lifetime while improving load balancing. It periodically collects scheduling matrix information form TSCH to compute a new measure for selecting the next hop at the network layer. More precisely, the parent with minimum number of occupied cells is more likely to be chosen as the preferred parent. To evaluate the performance of SA-RPL, we modified a distributed management scheme already developed in NS2 simulator. Simulation results show that SA-RPL, compared with other methods, prolongs the network lifetime up to two times and achieves a more uniform energy consumption distribution without decreasing other performance metrics.